Perancangan dan Pembuatan Aplikasi Sistem Informasi Administrasi pada UD. Duta Motor - Edwin Suwirno; Lily Puspa Dewi; Leo Willyanto Santoso (Jurnal Infra, 2015)
UD. Duta Motor is a commercial company that is engaged in the tools equipment sales for motor vehicles.In its business process, all administration are recorded manually, therefore, the risk of human error often occurs. This company requires information systems that provide administrative records therefore the works become more effective and efficient also to decrease the risk of human error.This application was created by using Microsoft Visual Studio 2005 VB. Net and SQL Server 2005 as the database storage system. The method used in the calculation of cost of goods sold is the average method. From the results of application's testing, it shows that the application can process the data directly related to the purchase and sale process automatically. Reports of sales, purchases and income statement can be done quickly and accurately.